Islamic Republic of Afghanistan : Selected Issues. (IMF Staff Country Reports; Country Report, 2008)
Fiscal sustainability is one of several policy objectives that Afghanistan is expected to achieve in the context of the Poverty Reduction Growth Facility-supported program. There is a need to develop a comprehensive financial sector strategy aimed at deepening financial intermediation and reducing key vulnerabilities. The aim of this paper is to analyze the conduct of monetary and exchange rate policy in Afghanistan. This paper also discusses the current monetary policy framework in Afghanistan, reviews its implementation, and recommends measures to improve its effectiveness.